Pelatihan Regulasi Emosi pada Remaja dalam Peningkatan Kemampuan Psikososial - Windu Astutik; Siti Kholifah (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background: Rapid development in adolescence is often problematic psychologically. Youth need the intelligence and emotional capacity to manage emotions to deal with the developments taking place to find a positive identity. Purpose: to improve knowledge among students about intelligence and emotional exercise regulations emotion at teenagers. Methods: The mental health education about intelligence and emotional regulation emotion among teenagers at SMP Negeri 15 Loajanan Samarinda. Education and training should be conducted by direct interaction with 60 students in class with matter the introduction of emotion, emotional intelligence, and training emotion in adolescents. The activity was carried out in 3 sessions with the following activities: the first session which was opened by the opening ceremony of the vice principal and the student, continued with a second session topic on the introduction of emotion, emotional intelligence, and training emotion in adolescents, and the third session is closing. Results: The implementation of the activities went well and smoothly. The results obtained are the increasing knowledge and psychomotor teenager emotional intelligence and emotion regulation. Conclusion: After a course of health education for adolescents, Adolescent ability to get to know emotions, Emotional intelligence, and the way emotional regulations are increasing so it's expected to increase the superior generation that has optimal mental health.